Training on Processing Local Food Lamtoro Beans to Become a Typical Culinary - Miftahal Anjarsabda Wira Buana; Muhammad Fathoni (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2023)
The successful facilitation of existing potential and resources necessitates robust and efficient assistance. The objective of this Community Service (PKM) is to assess the viability of utilising local food and community ingenuity in the processing and manufacturing of food items derived from local resources, with the ultimate goal of bolstering the economy. The local food development training programme conducted in Wae Bobok Village involved the collaboration of teachers and students from the eLBajo Commodus Polytechnic Hospitality Diploma Three Study Programme. This initiative aimed to assist the village residents in enhancing their local food offerings by transforming them into distinctive culinary creations that possess both appeal and increased worth. An interactive and practical training programme has been implemented to impart the necessary information and skills for the enhancement of local food into unique gourmet creations. During training sessions, individuals acquire knowledge pertaining to the selection of high-quality products, the techniques involved in food processing, and the creation of specialised menus. The objective of this training programme is to facilitate the residents of Wae Bobok Village in harnessing the untapped potential of indigenous food resources, thereby transforming them into captivating and high-value culinary offerings. Furthermore, it is anticipated that the outcomes of this endeavour would facilitate the emergence of novel employment and entrepreneurial prospects inside Wae Bobok Village. The implementation of this initiative aimed at transforming local produce into distinctive gourmet offerings is anticipated to enhance both food security and the local economy within Wae Bobok hamlet. Over time, this form of training can serve as a model for other rural communities in harnessing the inherent potential of indigenous food sources to create distinctive culinary offerings that are appealing and possess enhanced worth. In addition to this, the evolution of this characteristic gastronomic delight possesses the potential to serve as a viable tourist destination, thereby presenting prospects for the advancement of tourism centred around distinctive culinary offerings within Wae Bobok Village.